Confounding effect of EEG implantation surgery: Inadequacy of surgical control in a two hit model of temporal lobe epilepsy. (27th May 2016) - Balzekas, Irena; Hernandez, Jose; White, Jacob; Koh, Sookyong
Highlights: Cortical EEG screw electrode implantation increases susceptibility to kainic acid induced seizures. Electrode-implantation elicits non-negligible neuroinflammation that primes the immune response to future insults. Microglia activation by EEG implantation may only be uncovered after subsequent seizures. Abstract: In rodent models of epilepsy, EEG implantation surgery is an essential modality to evaluate electrographic seizures. The inflammatory consequences of EEG electrode-implantation and their resultant effects on seizure susceptibility are unclear. We evaluated electrode-implantation in a two-hit model of epileptogenesis in C57BL/6 mice that included brief, recurrent febrile seizures (FS) at P14 and kainic acid induced seizures (KA-SZ) at P28. During KA-SZ, latencies to first electrographic and behavioral seizures, seizure severity, and KA dose sensitivity were measured. Mice that received subdural screw electrode implants at P25 for EEG monitoring at P28 had significantly shorter latencies to seizures than sham mice, regardless of early life seizure experience. Electrode-implanted mice were sensitive to low dose KA as shown by high mortality rate at KA doses above 10 mg/kg. We then directly compared electrode-implantation and KA-SZ in seizure naive CX3CR1 GFP/+ transgenic C57BL/6 mice, wherein microglia express green fluorescent protein (GFP), to determine if microglia activation related to surgery was associated with the increased seizure susceptibility in electrode-implanted mice from the two-hit model. Hippocampal microglia activation, as demonstrated by percent area GFP signal and GFP positive cell counts, prior to seizures was indistinguishable between electrode-implanted mice and controls, but was significantly greater in electrode-implanted mice following seizures. Electrode-implantation had a confounding priming effect on the inflammatory response to subsequent seizures.